The Effect of Green Accounting, Environmental Management System, and Corporate Social Responsibility on Environmental Performance of Energy Sector Companies in 2021-2023 - Talitha Nabilah Putri; Dwi Suhartini (International Journal of Economics Development Research (IJEDR), 2024)
This research aims to empirically examine and analyze the influence of green accounting, environmental management systems, and corporate social responsibility on environmental performance. The population used is 77 energy sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period, with a sample size of 57 company data. The testing method uses partial least square (PLS) processed with SmartPLS for Windows Version 3.0. The test results show that the variables of green accounting, environmental management systems, and corporate social responsibility affect environmental performance.